Composite current collector, preparation method of composite current collector, pole piece and secondary battery

By setting up a polymer conductive layer and a metal conductive layer in the pole ear region of the current collector, the problem of mismatch between the dressing area and the pole ear region is solved, the risk of band breaking is reduced, and the energy density and rate performance of the battery are improved.

CN119905598APending Publication Date: 2025-04-29BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510172860.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

During the preparation of lithium-ion battery electrode sheets, the extension of the dressing area and the pole ear area does not match, resulting in stress concentration, causing belt breakage, and affecting the process yield.

Method used

The polymer conductive layer and the metal conductive layer are arranged in sequence in the pole ear region of the current collector. By forming a conductive layer structure in the pole ear region, the mechanical properties of the current collector are improved and the risk of breaking during the rolling process is reduced.

Benefits of technology

It reduces the risk of roller-pressure and belt breakage, ensures the high energy density of the battery, and improves the battery's rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905598A_ABST
    Figure CN119905598A_ABST
Patent Text Reader

Abstract

The invention relates to a composite current collector, a preparation method of the composite current collector, a pole piece and a secondary battery, the surface of the composite current collector comprises a dressing area for coating an active material, as well as tab areas and a reserved area which are positioned on the outer side of the dressing area, and the reserved area is positioned between two adjacent tab areas; and the tab area on at least one side surface of the composite current collector is sequentially provided with a polymer conductive layer and a metal conductive layer. The polymer conductive layer and the metal conductive layer are sequentially arranged in the tab area of the current collector, so that the risk of belt breakage caused by rolling can be reduced, the risk of belt breakage can be reduced while the high energy density of the battery is ensured, and the rate capability of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of batteries, and in particular, relates to a composite current collector, a preparation method of the composite current collector, a pole piece and a secondary battery. Background Art

[0002] Rolling is one of the key steps in preparing lithium-ion battery pole pieces. Its function is to compact the pole piece material to improve the energy density and cycle stability of the battery.

[0003] With the continuous development of the new energy vehicle industry, the market has put forward higher requirements for the energy density and endurance of batteries. This trend has pushed the aluminum foil material to develop in a thinner direction, thereby further improving the compaction density and surface density of the pole piece. However, during the rolling process, the material extension in the dressing area will drive the aluminum foil to extend synchronously, while the tab area will not extend accordingly, resulting in a mismatch between the extension of the dressing area and the tab area, which in turn generates stress concentration, causes the tape break phenomenon, and affects the process yield. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that the pole piece is prone to breakage during the preparation process and to improve the energy density and rate performance of the battery.

[0005] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a composite current collector, the surface of which includes a dressing area for coating active materials and a pole lug area and a reserved area located outside the dressing area, and the reserved area is located between two adjacent pole lug areas; the pole lug area on at least one side of the surface of the composite current collector is sequentially provided with a polymer conductive layer and a metal conductive layer.

[0006] Optionally, the polymer conductive layer is provided on the surface of the reserved area.

[0007] Optionally, the material of the polymer conductive layer is selected from one or more of polyacetylene, polyparaphenylene, polypyrrole, polythiophene, polypyridine, polyphenylene sulfide, polyaniline and polyphthalocyanine compounds; and / or the material of the metal conductive layer is selected from one or more of nickel, aluminum and stainless steel.

[0008] Optionally, the thickness of the polymer conductive layer is 2.0-5.0 μm.

[0009] Optionally, the thickness of the metal conductive layer is 8-25 μm.

[0010] Optionally, the current collector has a thickness of 8-15 μm.

[0011] Optionally, the dressing area on the surface of the composite current collector is coated with a conductive film; optionally, the conductive film is selected from one or more of graphite, conductive carbon black, carbon nanotubes and carbon fibers.

[0012] A second aspect of the present invention provides a method for preparing a composite current collector, the method comprising: Coating a conductive polymer material on the tab region of at least one side of the current collector surface, and heating and curing the material to form a polymer conductive layer in the tab region; A metal conductive layer is formed on the surface of the polymer conductive layer in the tab region.

[0013] Optionally, the method further comprises: coating a conductive polymer material on a reserved area on at least one side of the current collector surface, and heating and curing the conductive polymer material in the reserved area; the reserved area is arranged between two adjacent tab areas.

[0014] Optionally, the method for forming the metal conductive layer is selected from one or a combination of laser cladding and cold spraying; wherein the average particle size of the metal raw material used for the cold spraying is 0.5-5 μm.

[0015] Optionally, the method further comprises: coating a conductive film on a dressing area on at least one side surface of the current collector.

[0016] A third aspect of the present invention provides a pole piece, which comprises the composite current collector described in the first aspect of the present invention and an active material layer arranged in the dressing area.

[0017] A fourth aspect of the present invention provides a secondary battery, the secondary battery comprising the electrode sheet according to the third aspect of the present invention Through the above technical scheme, the present invention can reduce the risk of belt breakage during rolling by sequentially arranging a polymer conductive layer and a metal conductive layer in the ear region of the current collector, can reduce the risk of belt breakage while ensuring the high energy density of the battery, and can also improve the rate performance of the battery.

[0018] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 is a top view of the current collector in some embodiments of the present invention.

[0020] Figure 2 Schematic diagram of the structure of the composite current collector in some embodiments of the present invention.

[0021] Figure 3 It is a schematic diagram of the structure of the pole piece in some embodiments of the present invention.

[0022] Marking Description: 110. Current collector; 111. Tab area; 112. Reserved area; 113. Dressing area; 121. Polymer conductive layer in the tab area; 122. Polymer conductive layer in the reserved area; 130. Metal conductive layer; 210. Active material layer. DETAILED DESCRIPTION

[0023] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0024] In the prior art, the maximum force that the current collector can withstand is relatively small, and it is easy to deform during the rolling process, which increases the rolling extension of the pole piece, making the matching between the extension of the pole ear area and the dressing area worse, and increasing the risk of belt breakage. The thinner the aluminum foil, the more defects there will be on the aluminum foil. For example, the presence of surface defects such as pinholes, surface roller marks, abrasions, and scratches will deteriorate the elongation of the aluminum foil, further increase the risk of belt breakage, and limit the use of thinner aluminum foil in battery technology. On the other hand, as the thinner the aluminum foil, the greater the current capacity, the greater the internal resistance of the battery, resulting in a decrease in the charging and discharging efficiency of the battery. Based on this, the present invention is proposed.

[0025] The first aspect of the present invention provides a composite current collector, the surface of which includes a dressing area for coating active materials, and a pole lug area and a reserved area located outside the dressing area, and the reserved area is located between two adjacent pole lug areas; the pole lug area on at least one side of the surface of the composite current collector is sequentially provided with a polymer conductive layer and a metal conductive layer.

[0026] The present invention can reduce the risk of belt breakage during rolling by sequentially arranging a polymer conductive layer and a metal conductive layer in the lug region of the current collector, can reduce the risk of belt breakage while ensuring a high energy density of the battery, and can also improve the rate performance of the battery.

[0027] Figure 1 The top view of the current collector is shown schematically. Figure 1 In the structure shown, the surface of the current collector 110 includes a dressing area 113 for coating active materials, and a plurality of pole ear areas 111 for connecting to the adapter sheet are arranged on the outside of the dressing area 113, and the area between two adjacent pole ear areas 111 along the same side direction of the outside of the dressing area is a reserved area 112.

[0028] according to Figure 2 As shown in the structural schematic diagram of the composite current collector, in the composite current collector of the present invention, the tab region on the surface of the current collector 110 is sequentially provided with a polymer conductive layer 121 and a metal conductive layer 130 .

[0029] In some embodiments of the present invention, the surface of the reserved area is provided with the polymer conductive layer. Figure 3 The schematic diagram of the structure of the pole piece shown in the figure shows that the reserved area surface is also provided with a reserved area polymer conductive layer 122. The lug area polymer conductive layer 121 and the reserved area polymer conductive layer 122 can be formed by coating the surface of the current collector at the same time, and then only the metal conductive layer is provided on the surface of the lug area polymer conductive layer.

[0030] In some embodiments of the present invention, the material of the polymer conductive layer is selected from one or more of polyacetylene, polyparaphenylene, polypyrrole, polythiophene, polypyridine, polyphenylene sulfide, polyaniline and polyphthalocyanine compounds. The polymer conductive layer provided by the present invention can increase the threshold of the current collector layer to withstand stress and reduce the risk of belt breakage during rolling.

[0031] In the present invention, the material of the polymer conductive layer is selected from polyacetylene, polyparaphenylene, polypyrrole, polythiophene, polypyridine, polyphenylene sulfide, polyaniline and polyphthalocyanine compounds. These polymer materials usually have a conjugated structure in their molecular structure, which can provide a path for electrons to move within or between molecules, thereby achieving conductivity. Traditional insulating polymer materials (such as polyurethane, polyvinyl alcohol, polymethyl methacrylate, polymethyl acrylate, polyethylene oxide, polyethylene glycol, polyvinyl chloride, polyamide, etc.) are coated on the surface of the current collector mainly for insulation protection, mainly providing mechanical support and protection, and increasing the internal resistance of the battery.

[0032] In some embodiments of the present invention, the thickness of the polymer conductive layer is 2.0-5.0 μm. The polymer conductive layer has an appropriate thickness, which is beneficial to improving the mechanical properties of the current collector and does not affect the conductivity of the current collector, the conductivity of the battery, and the rate performance. For example, the thickness of the polymer conductive layer can be 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm. If the thickness of the polymer conductive layer is too large or too small, the mechanical properties of the composite current collector tab region will be reduced, and the conductivity will also be affected. The greater the thickness of the polymer conductive layer, the greater the square resistance of the composite current collector tab region, the greater the internal resistance of the battery, and the rate performance of the battery is reduced. When the thickness of the polymer conductive layer is too small, the bonding force between the metal conductive layer and the polymer conductive layer in the composite current collector tab region decreases, and the risk of band breakage is increased, which reduces the rate performance of the battery.

[0033] In some embodiments of the present invention, the material of the metal conductive layer is selected from one or more of nickel, aluminum and stainless steel. By selecting the above metal materials with excellent electrical conductivity and tensile strength to form the metal conductive layer, the threshold of the bearing capacity of the current collector tab area can be further increased, the risk of belt breakage can be reduced, and the process yield can be improved.

[0034] In some embodiments of the present invention, the thickness of the metal conductive layer is 8-25 μm, for example, it can be 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm or any value within the aforementioned range, or a range between any two values. The metal conductive layer has a suitable thickness, which can improve the bonding force between the polymer conductive layer and the metal conductive layer, improve the tensile strength of the composite current collector tab area, and improve the rate performance of the battery. When the metal conductive layer is too thin, the bonding force between the metal conductive layer and the polymer conductive layer and the mechanical properties of the composite current collector tab area are significantly reduced, which is not conducive to improving the process yield of the battery and the electrochemical performance of the battery.

[0035] In some embodiments of the present invention, the thickness of the current collector is 8-15 μm, for example, it can be 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 11 μm, 12 μm, 14 μm, 15 μm or any value within the aforementioned range, or a range between any two values. The current collector has a suitable thickness to improve the bonding force between the metal conductive layer and the polymer conductive layer in the composite current collector lug region, improve the tensile strength of the composite current collector lug region, and improve the energy density of the pole piece and the lithium-ion battery. In addition, the structure of the composite current collector allows the use of a thinner current collector, thereby increasing the capacity of the battery. However, when the current collector is too thin, although it can increase the capacity of the lithium-ion battery, it will reduce the conductivity, increase the internal resistance, affect the rate performance and cycle life, and is very easy to break or deform during coating and rolling, increase the risk of short circuit, and reduce the process yield. If the current collector is too thick, the amount of active material used will be reduced, and the battery capacity will be reduced.

[0036] In some embodiments of the present invention, the dressing area on the surface of the composite current collector is coated with a conductive film, which can reduce the interface resistance, improve the electron transfer efficiency, reduce the internal resistance, and improve the performance of the battery at a high rate. The thickness of the conductive film and the coating area of ​​the conductive film in the dressing area are not limited, for example, it can be continuously or intermittently arranged in the dressing area on the surface of the current collector.

[0037] In some specific embodiments of the present invention, the conductive film is selected from one or more of graphite, conductive carbon black, carbon nanotubes and carbon fibers, so that the electrochemical performance and life of the battery can be significantly improved.

[0038] A second aspect of the present invention provides a method for preparing a composite current collector, the method comprising: Coating a conductive polymer material on the tab region of at least one side of the current collector surface, and heating and curing the coating to form a polymer conductive layer in the tab region; A metal conductive layer is formed on the surface of the polymer conductive layer in the tab region.

[0039] The present invention forms a polymer conductive layer and a metal conductive layer in sequence in the tab region on the surface of the current collector, thereby significantly improving the mechanical properties of the composite current collector, reducing the risk of tape breakage during coating and rolling, and not affecting the conductivity of the battery.

[0040] In some embodiments of the present invention, the method further comprises: coating a conductive polymer material on a reserved area on at least one side of the current collector surface, and heating and curing the conductive polymer material in the reserved area; the reserved area is arranged between two adjacent tab areas.

[0041] The polymer material can be coated on the lug area and the reserved area of ​​the current collector surface at the same time, baked and cured to form a polymer conductive layer, and then a metal conductive layer is provided only on the surface of the polymer conductive layer in the lug area. Specifically, the polymer material is selected from one or more of polyacetylene, polyparaphenylene, polypyrrole, polythiophene, polypyridine, polyphenylene sulfide, polyaniline and polyphthalocyanine compounds.

[0042] The metal conductive layer can be obtained by PVD, CVD, solid deposition, coating and laser cladding. In some preferred embodiments of the present invention, the method for forming the metal conductive layer can be selected from one or a combination of laser cladding and cold spraying, wherein laser cladding can deposit metal powder on the surface of the substrate with high precision, and is particularly suitable for substrates with complex shapes such as tabs; cold spraying accelerates the metal powder through high-pressure gas to impact the surface of the substrate at supersonic speed, and forms a dense coating through plastic deformation.

[0043] Among them, the average particle size (D v 50) is 0.5-5 μm, for example, the average particle size of the metal raw material can be 0.5 μm, 0.9 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm or any value within the aforementioned range, or a range between any two values. The metal powder used for cold spraying can be selected from one or more of nickel, aluminum and stainless steel. In the present invention, the metal raw material has the most uniform distribution of powder in the coating and the highest bonding strength. Taking aluminum powder as an example, if the particle size is too small, the aluminum powder is not easy to combine with the tab substrate, which leads to poor quality of the generated coating; in addition, if the particle size is too small, there will be insufficient energy to cause plastic deformation, resulting in easy detachment of the aluminum powder. If the particle size is too large, the internal strain distribution of the coating will be uneven, which will easily cause the aluminum foil tab to deform, affecting the performance and safety of the battery.

[0044] In some specific embodiments of the present invention, the working parameters for forming a metal conductive layer on the surface of the polymer conductive layer by cold spraying include: a nozzle distance of 20-40 mm; a spraying powder feed rate of 10-20 g / min; and a moving speed of the nozzle or the aluminum foil current collector of 80-120 mm / min, thereby forming a dense metal conductive layer on the surface of the polymer conductive layer.

[0045] In the present invention, compressed gas, such as helium, nitrogen or other inert gases, is required in the cold spraying process. Nitrogen is the best carrier gas due to its low price, good acceleration performance for particles and low impact on the environment. For example, the working temperature of nitrogen during cold spraying of aluminum is 100-200 °C and the working pressure of nitrogen is 4-5 MPa.

[0046] In some embodiments of the present invention, the method further comprises: coating a conductive film on a dressing area on at least one side of the surface of the current collector to improve the conductivity of the current collector.

[0047] In some preferred embodiments of the present invention, the method for preparing the current collector includes: (1) coating a conductive carbon layer on the dressing area on at least one side of the current collector, and coating a polymer conductive layer on the tab area and the reserved area, baking and curing, to obtain a current collector with a conductive layer on the surface; wherein the thickness of the polymer conductive layer is selected from 2-5 μm, and the thickness of the conductive carbon layer is 0.5-2 μm; (2) The surface of the polymer conductive layer in the tab region of the current collector surface is subjected to cold spray treatment to form a metal conductive layer on the surface of the polymer conductive layer in the tab region.

[0048] In step (1), the baking and curing temperature is 100-150°C and the time is 3-5 minutes. The coated polymer is cured so that the polymer is bonded to the surface of the current collector. The baking and curing makes the bonding force of the polymer conductive layer on the surface of the current collector greater than 5N.

[0049] In step (2), when the metal conductive layer is formed by spraying, the metal powder needs to be dried first to remove the moisture in the metal powder to avoid the moisture in the metal powder affecting the bonding quality of the sprayed material. At the same time, drying the metal powder pretreatment can also reduce defects in the metal conductive layer.

[0050] In the present invention, the aluminum powder is dried in a drying oven at a temperature between 100 and 150° C. for a drying time of 30 to 90 minutes. Inert gas such as argon needs to be introduced into the drying oven to prevent the aluminum powder from being oxidized.

[0051] A third aspect of the present invention provides a pole piece, which comprises the current collector described in the first aspect of the present invention and an active material layer arranged in the dressing area.

[0052] The present invention can prepare a wide range of battery types. The steps of preparing positive electrode sheets and batteries using cold-sprayed aluminum current collectors are conventional processes, including coating, rolling, slitting and die-cutting, lamination, welding and assembly.

[0053] Coating: The active material (lithium iron phosphate), binder (PVDF) and conductive agent (graphene, carbon black) are mixed to prepare a slurry, and then evenly coated on the non-ear area of ​​the aluminum foil (current collector of the positive electrode material) by a coating machine to form a positive electrode sheet; the negative electrode current collector, i.e. copper foil, is coated in the same way to form a negative electrode sheet. The single-sided coating thickness is generally controlled at 50-120 μm.

[0054] Roller pressing: The coated electrode sheet needs to be compacted by a roller press to increase the compaction density of the positive or negative electrode material. The purpose of roller pressing is to connect the active material and the foil together according to the set compaction density of the positive and negative electrode materials.

[0055] Slitting and die-cutting: After rolling, the pole piece needs to be processed into sheets of different sizes by slitting and die-cutting. During the slitting and die-cutting process, attention should be paid to the control of burrs and dust. After die-cutting, only the sprayed pole ear area should be retained.

[0056] A fourth aspect of the present invention provides a secondary battery, the secondary battery comprising the above-mentioned pole piece. The method for preparing the secondary battery generally comprises the steps of lamination, welding and assembly.

[0057] Stacking: The electrode sheets after slitting and die-cutting need to be stacked in the order of negative electrode, diaphragm, positive electrode, and diaphragm. The diaphragm separates the positive and negative electrodes, prevents internal short circuit of the battery, allows electrolyte ions to pass freely, and completes the electrochemical charge and discharge process.

[0058] Welding: Weld the positive and negative pole ears to the copper-aluminum adapter plate respectively by laser welding to ensure that the two pole ears are in parallel.

[0059] Assembly: Place the assembled battery cell into the battery case, inject an appropriate amount of electrolyte, and then perform formation treatment, i.e. the first charging process, to form the SEI film of the battery to ensure the stability and cycle performance of the battery.

[0060] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.

[0061] In the following examples and comparative examples, the thicknesses of the current collector, the polymer layer and the metal conductive layer were measured using a micrometer.

[0062] Example 1 This example is used to illustrate a method for preparing a composite current collector of the present invention, which comprises the following steps: (1) In Figure 1 The lug area and the reserved area on one side of the current collector aluminum foil are coated with a polyacetylene solution (DMA solution of polyacetylene, with a mass fraction of 5wt%), and a conductive carbon black layer is coated on the dressing area. The current collector coated with the conductive material is baked and cured at 120°C for 1 h to form a conductive carbon layer in the dressing area, and a polymer conductive layer is formed in the lug area and the reserved area. (2) Cold spraying the aluminum powder with a Dv50 particle size of 2.5 μm that has been dried onto the surface of the polymer conductive layer in the tab region to form a metal aluminum conductive layer on the surface of the polymer conductive layer in the tab region to obtain a composite current collector.

[0063] The working parameters during the spraying process include: nozzle distance of 30 mm; spray powder feeding amount of 15 g / min; nozzle or aluminum foil current collector moving speed of 100 mm / min. Nitrogen is used as compressed gas during spraying, and the working temperature of nitrogen during cold spraying is 150 °C and the working pressure of nitrogen is 4.5 MPa. The thickness of the current collector aluminum foil is 10 μm, the thickness of the polymer conductive layer is 2 μm, and the thickness of the metal aluminum conductive layer is 10 μm.

[0064] Example 2-13 The method for preparing the composite current collector in Example 2-13 is similar to that in Example 1, except that the thickness of the current collector, the polymer conductive layer and the metal conductive layer are different. Specific parameters are shown in Table 1.

[0065] Embodiment 14 Example 14 The method for preparing the composite current collector is similar to that of Example 1, except that the material of the polymer conductive layer is polythiophene.

[0066] Embodiment 15 Example 15 The method for preparing the composite current collector is similar to that of Example 14, except that the particle size Dv50 of the metal aluminum powder is 5.0 μm.

[0067] Example 16 Example 16 The method for preparing the composite current collector is similar to that of Example 14, except that the particle size Dv50 of the metal aluminum powder is 0.9 μm.

[0068] Comparative Example 1 Comparative Example 1 The method for preparing the composite current collector is similar to that of Example 1, except that the polymer material of the high-density conductive layer is replaced by polyacrylamide.

[0069] Comparative Example 2 Comparative Example 1 The method for preparing the composite current collector is similar to that of Example 1, except that the polymer material of the high-density conductive layer is replaced with polyacrylamide, and the polymer conductive layer is coated only on the tab area and the reserved area on the surface of the aluminum foil current collector.

[0070] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the composite current collector is an aluminum foil with a thickness of 10 μm.

[0071] Table 1

[0072] The performance parameters of the composite current collectors in Examples 1-16 and Comparative Examples 1-3 were tested by the following methods, respectively: The bonding force between the metal conductive layer and the polymer conductive layer (polymer layer): the peeling test is carried out on a universal testing machine, and the implementation standard refers to GB / T 5210-2006; Tensile strength of the composite current collector tab area: tested using a universal testing machine, with implementation standards referring to GB / T 228.1-2010; Defect level of the composite current collector tab area: tested using CCD online detection equipment; Conductivity of the composite current collector in the tab area: Use four probes to test the square resistance of the current collector in the tab area.

[0073] Table 2

[0074] It can be found from the data in the above table that the composite current collector of the present invention can significantly improve the mechanical properties of the composite current collector tab region, reduce defects, and can reduce the square resistance of the current collector.

[0075] The current collectors provided in Examples 1-16 and Comparative Examples 1-3 are coated with active materials, respectively, and rolled, slit and die-cut, laminated, welded and assembled to obtain a battery. The following is a detailed description of the lithium ion battery prepared using lithium iron phosphate as the active material.

[0076] Preparation of positive electrode slurry: The positive electrode active material lithium iron phosphate, the conductive agent carbon nanotubes, the binder PVDF and N-methylpyrrolidone (NMP) are mixed in a mass ratio of 100:2:3:50, and the organic solvent NMP is added and stirred at high speed to form a uniform dispersion; after the high-speed stirring, negative pressure defoaming is performed in a stirring tank to obtain a positive electrode slurry suitable for coating.

[0077] Preparation of negative electrode slurry: negative electrode active material graphite is mixed with conductive agent carbon black, binder and CMC in a mass ratio of 96.8:1.2:1.2:0.8 and added into deionized water and stirred at high speed to form a uniform dispersion; after high-speed stirring, negative pressure defoaming is performed in a stirring tank to obtain a negative electrode slurry suitable for coating.

[0078] Preparation of electrolyte: Under protective gas conditions, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) are mixed in a mass ratio of 1:1:1 to obtain an organic solvent; lithium salt LiPF6 is dissolved in the above organic solvent, and then fluoroethylene carbonate (FEC) is added and mixed evenly to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, the mass percentage of FEC is 5%, and the balance is the organic solvent.

[0079] Coating: The obtained positive electrode slurry was coated on the dressing area on both sides of the current collector obtained in the above Examples 1-15 and Comparative Examples 1-3 by a transfer coater, dried and rolled to obtain a positive electrode sheet with a compaction density of 2.6 g / cm 3 The negative electrode slurry was coated on the dressing area on both sides of the negative electrode current collector copper foil in the same way, dried and rolled to obtain the negative electrode sheet with a compaction density of 1.5 g / cm 3 The coating thickness of the active material layer on one side of the positive electrode sheet is 120 μm.

[0080] Slitting and die-cutting: The rolled pole pieces are processed into sheets of different sizes through slitting and die-cutting. After die-cutting, the reserved area of ​​the current collector is removed, leaving only the pole ear area.

[0081] Lamination: The electrode sheets after slitting and die-cutting are stacked in the order of negative electrode, separator, positive electrode, and separator. The separator is polypropylene with a thickness of 12 μm.

[0082] Welding: Connect the tabs of the positive electrode and the negative electrode to the copper-aluminum adapter by laser welding to ensure that the two tabs are connected in parallel.

[0083] Preparation of secondary batteries: Place the assembled battery core into the battery shell, inject an appropriate amount of electrolyte, and then perform formation treatment, that is, the first charging process, to form the SEI film of the battery to ensure the stability and cycle performance of the battery.

[0084] The performance and process yield of lithium-ion batteries made using the current collectors of Examples 1-16 and Comparative Examples 1-3 are analyzed below. The results are shown in Table 3.

[0085] (I) Battery DC internal resistance test: The batteries obtained in the examples and comparative examples were subjected to a battery DC internal resistance test, the test method comprising: charging the battery to 4.2V at 0.2C at 25°C, leaving it for 30 min, then discharging it at a discharge rate of 0.2C to a voltage of 2.5V, cycling it three times in sequence, taking the third charge and discharge data as the battery capacity; then charging it at 0.2C to 50% SOC, the voltage at this time being the voltage before discharge V0; placing the battery at 25°C, setting a 0.2C discharge for 30s, and recording the termination voltage (V i ) and termination current (I i ), calculate the DC resistance DCIR: DCIR (Ω) = (V0-V i ) / I i .

[0086] (II) Rate performance test: 1) At room temperature 25±5℃, discharge at 1 / 3C constant current to 2.0V / cell and leave for 30min; 2) Charging: Charge at 1C constant current to 3.8V / cell and leave for 1h; 3) Discharge: Discharge at 1 / 3C constant current to 2.0V / Cell.

[0087] (III) Battery capacity test: Standard charging: At room temperature 25±5℃, charge at 1 / 3C constant current to 3.8V / cell; leave for 30 minutes.

[0088] Standard discharge: at room temperature 25±5℃, 1 / 3C constant current discharge to 2.0V / cell; leave for 30min.

[0089] The battery was cycled for 3 times and the third discharge capacity was taken as the battery discharge capacity C0.

[0090] (IV) Process yield: the yield of the entire process from coating to battery cell production.

[0091] Table 3

[0092] Analysis of the data in the above table shows that, compared with the aluminum foil current collector in Comparative Example 3, the composite current collector provided by the present invention can significantly improve the process yield while ensuring the high energy density of the battery, and also improves the rate performance of the battery.

[0093] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0094] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0095] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A composite current collector, characterized in that: The surface of the composite current collector includes a dressing area for coating active materials, a tab area and a reserved area located outside the dressing area, and the reserved area is located between two adjacent tab areas; the tab area on at least one side of the surface of the composite current collector is sequentially provided with a polymer conductive layer and a metal conductive layer.

2. The composite current collector according to claim 1, wherein: The surface of the reserved area is provided with the polymer conductive layer.

3. The composite current collector according to claim 1 or 2, wherein: The material of the polymer conductive layer is selected from one or more of polyacetylene, polyparaphenylene, polypyrrole, polythiophene, polypyridine, polyphenylene sulfide, polyaniline and polyphthalocyanine compounds; and / or, The material of the metal conductive layer is selected from one or more of nickel, aluminum and stainless steel.

4. The composite current collector according to claim 1 or 2, wherein: The thickness of the polymer conductive layer is 2.0-5.0 μm.

5. The composite current collector according to claim 1 or 2, wherein: The thickness of the metal conductive layer is 8-25 μm.

6. The composite current collector according to claim 1, wherein: The thickness of the current collector is 8-15 μm.

7. The composite current collector according to claim 1, wherein: The dressing area on the surface of the composite current collector is coated with a conductive film; Optionally, the conductive film is selected from one or more of graphite, conductive carbon black, carbon nanotubes and carbon fibers.

8. A method for preparing a composite current collector, characterized in that: The method includes: Coating a conductive polymer material on the tab region of at least one side of the current collector surface, and heating and curing the coating to form a polymer conductive layer in the tab region; A metal conductive layer is formed on the surface of the polymer conductive layer in the tab region.

9. The method according to claim 8, wherein: The method further comprises: coating a conductive polymer material on a reserved area on at least one side of the current collector surface, and heating and curing the conductive polymer material in the reserved area; The reserved area is arranged between two adjacent tab areas.

10. The method according to claim 8, wherein: The method of forming the metal conductive layer is selected from one or a combination of laser cladding and cold spraying; Wherein, the average particle size of the metal raw material used for the cold spraying is 0.5-5 μm.

11. The method according to claim 8, wherein: The method further comprises: coating a conductive film on a dressing area on at least one side surface of the current collector.

12. A pole piece, characterized in that: The pole piece comprises the composite current collector according to any one of claims 1 to 7 and an active material layer arranged in the dressing area.

13. A secondary battery, characterized in that: The secondary battery comprises the electrode sheet according to claim 12.